2004
DOI: 10.1016/s0165-0327(03)00098-3
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive-behavioral therapy, light therapy, and their combination in treating seasonal affective disorder

Abstract: Background: The need to develop supplementary or alternative treatments for seasonal affective disorder (SAD) is underscored by the significant minority (47%) of SAD patients that is refractory to light therapy, the persistence of residual symptoms despite light treatment, and poor long-term compliance with light use. Because preliminary studies suggest that cognitive and behavioral factors are involved in SAD, cognitive-behavioral therapy (CBT) warrants investigation as a possible treatment option. Methods: W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
51
0
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 50 publications
(54 citation statements)
references
References 32 publications
2
51
0
1
Order By: Relevance
“…Of most relevance would be cognitive behavioural therapy (CBT) for which there is a large evidence base for its use in other mood disorders. Preliminar y data by Rohan et al 50,51 suggest that a tailored course of CBT is as efficacious as light therapy in the acute phase and better at preventing relapse; 52 however, there is a clear need for further study.…”
Section: Key Pointsmentioning
confidence: 99%
“…Of most relevance would be cognitive behavioural therapy (CBT) for which there is a large evidence base for its use in other mood disorders. Preliminar y data by Rohan et al 50,51 suggest that a tailored course of CBT is as efficacious as light therapy in the acute phase and better at preventing relapse; 52 however, there is a clear need for further study.…”
Section: Key Pointsmentioning
confidence: 99%
“…Third, we used data from a pilot clinical trial (Rohan et al, 2004), which was underpowered and not designed to inform researchers about the course of SAD. The lack of significant differences among treatments using the QALY(G) scores may have reflected lack of power and not lack of treatment differences, as Rohan et al, reported significant treatment group differences at her 1-year follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…The pilot data showing the efficacy of CBT for SAD can be found in Rohan et al (2004). To summarize, Rohan et al found no difference among the conditions at post-treatment, but BDI-II scores were significantly more favorable for participants in CBT and CBT + LT, when compared to LT at the one-year winter follow up.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations